Potential host fruits for Drosophila suzukii: olfactory and oviposition preferences and suitability for development. Issue 10 (16th October 2019) - Cai, Pumo; Song, Yunzhe; Yi, Chuandong; Zhang, Qiwen; Xia, Huimin; Lin, Jia; Zhang, Hehe; Yang, Jianquan; Ji, Qinge; Chen, Jiahua
Abstract: Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), the spotted wing drosophila, is a pest endemic to Southeast Asia that invaded the Americas and Europe in 2008. In contrast to most of its congeners, D. suzukii possesses a serrated ovipositor that allows it to lay eggs in unwounded commercial fruits, resulting in severe revenue losses for the industry. The purpose of this study was to determine the susceptibility of known host fruits, including cherry, strawberry, blueberry, and grape, and potential host fruits, such as banana and apple, to attack by D. suzukii . Based on the responses to volatile cues offered in a six‐choice olfactometer, the preference of female D. suzukii was ranked in the following order: strawberry = cherry > banana = apple = blueberry = grape, but in no‐choice and choice oviposition tests, the preferences were ranked as follows: cherry > strawberry = blueberry > grape = banana > apple. Furthermore, we reconfirmed that D. suzukii mainly targets rotten fruit for feeding and ripe fruit for oviposition, and females preferred fruits with intensive mechanical damage. Based on developmental parameters, apple was the least suitable host. This study has implications for the control of D. suzukii, especially in mixed fruit orchards, by providing a promising avenue for exploiting behaviour‐based control tools and emphasizing the importance of phenology in host fruit susceptibility. Abstract : The susceptibility of the fruits of strawberry, blueberry, cherry, grape, apple, and banana to attack by Drosophila suzukii (Diptera: Drosophilidae) was evaluated based on the fruit fly's odour preferences, oviposition, and development. In addition, the olfactory preferences and oviposition of D. suzukii associated with various fruit types and stages of ripeness were studied. Apple turns out to be the least suitable host, and it is confirmed that the flies mainly target rotten and ripe fruits.